SERUM ADIPOKINES AND ADIPOKINE RECEPTORS IN COLON CANCER PATIENTS WITH METABOLOC SYNDROM - N. V. Yunusova; I. V. Kondakova; S. G. Afanasyev; О. V. Shatokhina; N. P. Kovalyeva; А. Е. Frolova; Е. S. Kolegova (Сибирский онкологический журнал, 2016)
Purpose: to study serum adipokine levels and AdipoR1, AdipoR2 and sOb-R expressions with respect to clinical-morphological parameters and the evidence of metaboloc syndrome (MS) in patients with stage I–III colon cancer.Materials and methods. The study included 31 colon cancer patients having metabolic syndrome and patients having no metabolic syndrome. Serum levels of leptin, adiponektin, AdipoR1, AdipoR2 and soluble form of the leptin receptor was assessed by ELISA.Results and conclusion. The incidence of MS in colon cancer patients was 71 %. The relationship between the serum leptin level and gender and disease stage was revealed. The tendency toward increase in the leptin level in patients with MS was shown. The Ob-R level was higher in patients having no MS. The levels of AdipoR1 and AdipoR2 were significantly higher in female colon cancer patients. Adiponectin receptors tended to increase in colon cancer patients with MS.